Tension in a value co-creation context: a network case study - Tóth, Zsófia; Peters, Linda D.; Pressey, Andrew D.; Johnston, Wesley J. (Elsevier, 2018)
This study addresses tension and its consequent hurdles to the collaborative nature of value co-creation. Substantial research has focused on the benefits of value co-creation but much less so on its dark side. While some tension is inevitable, escalated tension can harm anticipated value and business relationships. The overlaps and disparities of formal and informal communication networks of two large construction projects are examined along with the tensions arising. To increase the breadth and depth of the empirical investigation, the presented network case study draws on survey data analyzed with Social Network Analysis as well as 45 in-depth managerial interviews. Structural, emotional and behavioural tensions are identified. The study suggests that tension triggered by one or a few actors can destabilize the network by creating unsustainable communication structures. Social Balance Theory is applied to study how unsustainable communication structures seek balance at a network level. We identify network patterns that can signal the presence of tension and structural imbalance in value co-creation, categorize several types of tension, and provide managerial implications.